Attentional bias and its temporal dynamics among war veterans suffering from chronic pain: Investigating the contribution of post-traumatic stress symptoms. (August 2019) - Mazidi, Mahdi; Vig, Kelsey; Ranjbar, Seyran; Ebrahimi, Mohammad-Reza; Khatibi, Ali
Highlights: Chronic pain is highly comorbid with PTSD symptoms in war veterans. Attentional bias in pain is suggested to be relevant to anxiety in chronic pain. Veterans showed a greater attentional bias away from pain-related cues. Avoidance from pain may indicate suppression of emotion in stressful situations. Veterans showed significantly elevated attentional bias variability for both happy and pain faces compared to controls. Abstract: Background: Cognitive models propose that attentional dysregulation, including an attentional bias towards threat, is one of the factors through which chronic pain and post-traumatic stress symptoms (PTSS) maintain and exacerbate one another. The current investigation assessed the attentional bias for painful facial expressions and its relationship with PTSS, using both traditional and variability-based attentional bias measures, among veterans with chronic pain and PTSS and controls. Method: Fifty-four veterans with chronic pain and 30 age/education-matched controls participated in this investigation. Participants completed a self-report measure of PTSS and a modified version of the dot-probe task with painful, happy, and neutral facial expressions. Attention was assessed using both traditional and variability-based reaction time measures of attentional bias. Results: Veterans directed attention away from painful facial expressions (i.e., avoidance) relative to both the control group (between-subject effect) and relative to neutral faces (within-subject effect). Veterans also showed significantly elevated attentional bias variability for both happy and painful facial expressions compared to controls. Attentional bias variability for happy and painful facial expressions was correlated with PTSS among all participants. Conclusion: Veterans with chronic pain and PTSS avoided pain-related stimuli and displayed an overall attentional dysregulation for emotional facial expressions. Avoidance of pain cues may be a coping strategy that these individuals develop under stressful conditions. Implications, limitations, and directions for future research are discussed.